Biết \(\displaystyle\int(x+3)\cdot\mathrm{e}^{-3x+1}\mathrm{\,d}x=-\dfrac{1}{m}\mathrm{e}^{-3x+1}(3x+n)+C\) với \(m,\,n\) là các số nguyên. Tính tổng \(S=m+n\).
\(10\) | |
\(1\) | |
\(9\) | |
\(19\) |
Chọn phương án D.
Đặt \(\begin{cases}
u&=x+3\\
v'&=\mathrm{e}^{-3x+1}
\end{cases}\Rightarrow\begin{cases}
u'&=1\\
v&=-\dfrac{1}{3}\mathrm{e}^{-3x+1}.
\end{cases}\)
Khi đó ta có $$\begin{aligned}
&\,\displaystyle\int(x+3)\cdot\mathrm{e}^{-3x+1}\mathrm{\,d}x\\
=&\,-\dfrac{1}{3}(x+3)\cdot\mathrm{e}^{-3x+1}-\displaystyle\int\left(-\dfrac{1}{3}\mathrm{e}^{-3x+1}\right)\mathrm{\,d}x\\
=&\,-\dfrac{1}{3}(x+3)\cdot\mathrm{e}^{-3x+1}+\dfrac{1}{3}\displaystyle\int\mathrm{e}^{-3x+1}\mathrm{\,d}x\\
=&\,-\dfrac{1}{3}(x+3)\cdot\mathrm{e}^{-3x+1}-\dfrac{1}{9}\mathrm{e}^{-3x+1}+C\\
=&\,-\dfrac{1}{9}(3x+10)\cdot\mathrm{e}^{-3x+1}+C.
\end{aligned}$$
Từ đó suy ra \(m=9\), \(n=10\).
Vậy \(S=9+10=19\).